Strategic human resource management in facilitating the organizational performance: Birds-eye view from Bangladesh - Md. Mahfuzur Rahman Khan (goodwood publishing, 2020)
Purpose: This study systematically explores and elaborates on strategic human resources management practices inside a company facilitating the intermediate variables of organization performance. Research methodology: Ten organizations with more or less similar yearly turnover and the same number of permanent employees have been used for this study. The analysis technique in this study uses data analysis developed by Miles et al. (2018) as follows; (a) data collection (b) data display and (c) concluding. Focus group discussions with the employees and management of those companies are being taken with the help of a semi-structured questionnaire. Results: The study's findings offered that the more strategic a company is with its human resource, the more turnover it can make, even if it has a similar number of human resources. Limitations: There are shortcomings in theoretical research on the process of strategic human resource management practices affecting organization performance. Contribution: This study offers a view to integrate and construct strategic human resource management activities affecting organization performance and provides a reasonable explanation and enlightenment for the understanding of further contribution.